Virtual Reality Environment with Haptic Feedback Thimble for Post Spinal Cord Injury Upper-Limb Rehabilitation - Álvaro Gutiérrez; Nicola Farella; Ángel Gil-Agudo; Ana de los Reyes Guzmán (Applied Sciences, 2021)
Cervical spinal cord injury is damage to the spinal cord that causes temporary or permanent changes in body functions below the site of the injury. In particular, the impairment of the upper limbs limits the patient’s autonomy in the execution of activities of daily living. This paper illustrates the use of a low-cost robot with a virtual reality platform for upper limb rehabilitation of cervical spinal cord injury patients. Vibration and pressure haptic feedback sensations are provided thanks to a custom-made thimble feedback device. The virtual reality platform consists of three different virtual rehabilitation games developed in Unity. They provide the user with the opportunity to interact with the virtual scene using free hands thanks to the data collected by a hand tracking system. During the therapy session, quantitative data about the motor performance are collected. Each virtual reality environment can be modified in settings according to the patients’ needs. A proof of concept was performed with both healthy subjects and spinal cord injured patients to evaluate the platform and its usability. The data saved during the sessions are analyzed to validate the importance of haptic feedback and stored both for patients and therapists to control the performance and the recovery process.